Antimicrobial activity and safety applications of meso-tetra(4-pyridyl)platinum(II) porphyrin. (March 2019) - Soares Lopes, Leonardo Quintana; Ramos, Andiara Prates; Copetti, Priscila Marquezan; Acunha, Thiago Vargas; Iglesias, Bernardo Almeida; Vianna Santos, Roberto Christ; Machado, Alencar Kolinski; Sagrillo, Michele Rorato
Abstract: Tetra-platinated(II) porphyrin hexafluorophosphate compound (4-PtTPyPor) was synthetized and along 5, 10, 15, 20-tetrakis(4-pyridyl)porphyrin (4-TPyPor), evaluated about the antimicrobial activity and safety. The effect was evaluated with and without light exposition. The antimicrobial activity was analyzed by microdilution and growth curve method. The assays showed an increase of antimicrobial potential caused by porphyrins with light exposition comparing the treatment without light irradiation. The biocompatibility was tested by MTT, ROS production, dsDNA on culture medium and hemolysis. All platinum porphyrin concentrations showed hemolytic activity under light exposition. The ROS measurement doesn't showed statistic difference between treatments and control. The picogreen assay demonstrates a reduction of dsDNA on culture medium with cells treated with porphyrins under light irradiation. The study demonstrated that the platinated porphyrins might be promising microbial photodynamic inactivation with potential applications in wastewater treatment, biofilm control and bioremediation. Highlights: The Tetra-platinated(II) porphyrin showed antimicrobial activity. Both porphyrins were more effective in presence of light against Staphylococcus aureus . The present study showed that porphyrins with platinum were effective against multi-resistant bacteria.